Piezoelectric micromachined ultrasonic transducer (pMUT) using adhesive wafer bonding for underwater applications - Jamilah Wardah Harun (Tanjong Malim, 2024)
Piezoelectric micromachined ultrasonic transducer (pMUT) using adhesive wafer bonding for underwater applications by Jamilah Wardah Harun